Ballas Water and Sediment Control and Management on Ship Using Method D-2: Auto Filter and UV Disinfection Treatment Methods - Yulian Arpianto; Hanna (Global Writing Academica Researching and Publishing, 2023)
This study aims to protect the maritime environment from the spread of foreign species or harmful aquatic organisms and pathogens due to the discharge of ballast water from ships in order to prevent, minimize and completely eliminate risks to the environment, human health, wealth and resources arising from the transfer of aquatic organisms. harmful and pathogenic through the control and management of ballast water and sediment from ships, as well as to avoid unwanted side effects from such control and to encourage the development of related science and technology. The problems raised in this study are (1) What is the Ballast Water Exchange Standard (Reg. D-1), (2) What is the Ballast Water Performance Standard (Reg. D-2)?, (3) What is the Ballast Water Management Plan (BWMP) (Rule B-1) and (4) What is the combination of treatment technology. The method used in this research is descriptive qualitative method using data reduction analysis techniques, data presentation, and drawing conclusions as a method to determine the causes and efforts to overcome them. The results show that by applying the Ballast Water Performance Standard (Reg.D-2) with a combination of treatment technology, it can protect the maritime environment with the required ballast water performance standards. As required in the convention concerning the control and management of ballast water and sediment from ships/The International Convention for The Control and Management of Ship's Ballast Water and Sediments, 2004, in this convention it is required that ships of 400 gross tonnage and above are subject to this convention, not including floating platforms, FSUs and FPSOs are required to participate in the survey determined and meet the requirements of the BWM Convention. The conclusion of this study is that by installing BWMT to meet Reg. D-2 can protect the maritime environment from the spread of foreign species or aquatic organisms and pathogens.